PENERAPAN METODE PEMBELAJARAN AKTIF LEARNING STARTS WITH A QUESTION (LSQ) UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN STRUKTUR ATOM DI KELAS X SMA NEGERI 11 PEKANBARU - Namirah Iskandar Namirah Iskandar; Elva Yasmi Amran Yasmi Amran; Erviyenni ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The research on application of active learning method Learning Starts With A Question (LSQ) has been done to improve of student achievement on the subject of Atomic Structure in class X SMAN 11 Pekanbaru. Form of the research is experimental research with pretest-posttest design. The sample consist of two classes, namely class X IPA 4 as the experimental and class X IPA 2 as control class which randomly selected after had tested normality and homogeneity. Experiment class was given implementing active learning method Learning Starts With A Question (LSQ) while the control class was not given implementing active learning method Learning Starts With A Question (LSQ). Data analysis technique used the t-test. Based on the result of the final data processing t-test formula obtained tarithmetic>ttable (1,97 > 1,67) means the application of active learning method Learning Starts With A Question (LSQ) can improve student achievement on the subject of Atomic Structure in class X SMAN 11 Pekanbaru, with an increase of 5,59%. Key Words : Learning Starts With A Question (LSQ), Learning Achievement, Atomic Structure.